COMPORTEMENT ALIMENTAIRE DES ADOLESCENTS : RESULTATS D’UNE ENQUETE DANS LE DEPARTEMENT DE SIDI BEL ABBES (ALGERIE OCCIDENTALE) - Ayad, Nadira; Hellal, Benchaben; Zidane, Nadia; Hellal, Tijania (European Scientific Journal, ESJ, 2014)
Feeding behavior of adolescents. Results of a survey in the department of Sidi Bel Abbes (Western Algeria) Objectives. The purpose of this study is to evaluate the feeding behavior of teenagers through a survey in the department of Sidi Bel Abbes (Western Algeria). Our examination used to estimate the quantity and quality of ingested food as well as their frequency. Methodology. This is a sample survey conducted from April 8 to 14, 2013. It involved 380 adolescents of both sexes, aged 12-19 years and residents in the town of Sidi Bel Abbes. The evaluation parameters used were: weight, size and nutrient intakes. Results.The fourcategories of adolescentsstudiedare deficient inweight with alack ofsize compared torecommended standards.The results of the average daily intakes of nutrients from the diet of adolescents were between 50 and 63 g / d for total protein and were insufficient to lipids (40 and 50 g / d) and total dietary fiber (20 - 27 g / d) against the carbohydrate intake was significantly high (344-418 g / d). The contributions of non-energy nutrients: Ph (1307 - 1540 mg / d), Fe (12-18 mg / d), Zn (13-15 mg / d) were sufficiently covered while the Ca (834-905 mg / day) showed some deficiency. Intakes of vitamins showed variable rates. The average energy level provided by the diet (1980 - 2380 kcal / d) was very low with a remarkable excess carbohydrates (1376 - 1673 kcal / d), about 70 % of total energy intake. Finally, the results of the energy intake of different meals showed a significant impairment (12.7 %) for breakfast. Conclusion. It appears that the feeding behavior of our teenagers accused imbalance and lack of obvious nutrition education. With regard to this situation and to better feed young people and preserve their health, it is desirable that prevention programs and nutrition education are quickly put in place.